Noun plural production in preschoolers with early cochlear implantation: An experimental study of Dutch and German. Issue 4 (April 2015) - Laaha, Sabine; Blineder, Michaela; Gillis, Steven
Abstract Objectives Studies investigating language skills of children after cochlear implantation usually present general measures of expressive/receptive vocabulary and grammar and rarely tackle the acquisition of specific language phenomena (word classes, grammatical constructions, word forms, etc.). Furthermore, research is largely restricted to children acquiring English. Cross-linguistic comparisons among children acquiring different languages are almost inexistent. The present study targets the acquisition of noun plurals (e.g., dogs, balls) by Dutch- and German-speaking children implanted before their second birthday. Given its structural complexity and irregularity, noun plural formation is a good indicator of grammatical proficiency in children at risk for a developmental delay. Methods The study sample consisted of 14 cochlear-implanted (CI) children (M = 55 months of age), 80 age-matched normally hearing (NH) controls, and 40 normally hearing controls matched by Hearing Age (HA). The children were administered an elicitation task in which they had to provide plural forms to a set of singular nouns. The analysis focussed on the following variables: Hearing status (CI, NH), Language (Dutch, German), and Suffix Predictability/Stem Transparency of the plural words. Results There was no significant difference between children with CI and their NH peers in correct plural production. In both child groups, plural responses followed the predicted pattern of Suffix Predictability/Stem Transparency. However, children with CI significantly more frequently replied to the test item with a recast of the singular noun instead of the plural, and the probability of these responses increased with later age of CI implantation. Furthermore, Dutch-speaking children showed an overall better performance than German-speaking children. Conclusions The findings suggest that after 3 years of implant use, preschoolers with early cochlear implantation show age-appropriate patterns of noun plural formation, but still have to catch up with respect to associating a particular singular with its plural form.